Co-design approach in developing oral health applications for school age children: Pendekatan co-design dalam pengembangan aplikasi kesehatan mulut untuk anak usia sekolah - Abigayl, Ivana; Darwita , Risqa Rina; Adiatman, Melissa (Makassar Dental Journal, 2025)
Oral health promotion among school age children requires innovative and engaging strategies to address persistent challenges such as dental caries and poor hygiene practices. Co-design methodology emphasizes the active involvement of end user chil-dren, parents, teachers, and health professionals in developing interventions tailored to their needs and context. This study re-views the use of a co-design approach in developing a school-based digital health application to improve oral health behaviors in children. The review examined stakeholder involvement, including children, parents, teachers, and health professionals in sha-ping content, usability, and engagement features of oral health applications. Evidence indicates that co-design enhances the re-levance, usability, and acceptability of digital oral health interventions by integrating the lived experiences and preferences of tar-get users. Applications developed through co-design showed higher levels of engagement, improved oral health knowledge, and better adherence to preventive behaviors among school children. It is concluded that co-design enhances the relevance, usabi-bility, and acceptability of digital oral health interventions by integrating the lived experiences and preferences of target users.